Software annotation of deﬁbrillator files: Ready for prime time?. (March 2021) - Gupta, Vishal; Schmicker, Robert H.; Owens, Pamela; Pierce, Ava E.; Idris, Ahamed H.
Abstract: Background: High-quality chest compressions are associated with improved outcomes after cardiac arrest. Deﬁbrillators record important information about chest compressions during cardiopulmonary resuscitation (CPR) and can be used in quality-improvement programs. Defibrillator review software can automatically annotate files and measure chest compression metrics. However, evidence is limited regarding the accuracy of such measurements. Objective: To compare chest compression fraction (CCF) and rate measurements made with software annotation vs. manual annotation vs. limited manual annotation of deﬁbrillator ﬁles recorded during out-of-hospital cardiac arrest (OHCA) CPR. Methods: This was a retrospective, observational study of 100 patients who had CPR for OHCA. We assessed chest compression bioimpedance waveforms from the time of initial CPR until deﬁbrillator removal. A reviewer revised software annotations in two ways: completely manual annotations and limited manual annotations, which marked the beginning and end of CPR and ROSC, but not chest compressions. Measurements were compared for CCF and rate using intraclass correlation coefficient (ICC) analysis. Results: Case mean rate showed no significant difference between the methods (108.1–108.6 compressions per minute) and ICC was excellent (>0.90). The case mean (±SD) CCF for software, manual, and limited manual annotation was 0.64 ± 0.19, 0.86 ± 0.07, and 0.81 ± 0.10, respectively. The ICC for manual vs. limited manual annotation of CCF was 0.69 while for individual minute epochs it was 0.83. Conclusion: Software annotation performed very well for chest compression rate. For CCF, the difference between manual and software annotation measurements was clinically important, while manual vs. limited manual annotation were similar with an ICC that was good-to-excellent.